2012
DOI: 10.1039/c2ob06611d
|View full text |Cite
|
Sign up to set email alerts
|

Aryne [3 + 2] cycloaddition with N-sulfonylpyridinium imides and in situ generated N-sulfonylisoquinolinium imides: a potential route to pyrido[1,2-b]indazoles and indazolo[3,2-a]isoquinolines

Abstract: The aryne [3 + 2] cycloaddition process with pyridinium imides breaks the aromaticity of the pyridine ring. By equipping the imide nitrogen with a sulfonyl group, the intermediate readily eliminates a sulfinate anion to restore the aromaticity, leading to the formation of pyrido[1,2-b]indazoles. The scope and limitation of this reaction are discussed. As an extension of this chemistry, N-tosylisoquinolinium imides, generated in situ from N'-(2-alkynylbenzylidene)-tosylhydrazides via an AgOTf-catalyzed 6-endo-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…43 In the case of using arynes as dipolarophiles and pyridinium imides 148 with different electron-withdrawing groups on the imide nitrogen, it was found that the pyrido[1,2-b]indazoles 155 are obtained in high yields (Scheme 58) using the tosyl derivatives 154, whereas the benzoyl, pivaloyl, benzyloxycarbonyl, and tert-butyloxycarbonyl ones gave lower results. 90 This methodology has been also used with N-tosylisoquinolinium imides to afford indazolo[3,2-a]isoquinolines.…”
Section: Scheme 54 Preparation Of Fused Spirooxindoles 143mentioning
confidence: 99%
“…43 In the case of using arynes as dipolarophiles and pyridinium imides 148 with different electron-withdrawing groups on the imide nitrogen, it was found that the pyrido[1,2-b]indazoles 155 are obtained in high yields (Scheme 58) using the tosyl derivatives 154, whereas the benzoyl, pivaloyl, benzyloxycarbonyl, and tert-butyloxycarbonyl ones gave lower results. 90 This methodology has been also used with N-tosylisoquinolinium imides to afford indazolo[3,2-a]isoquinolines.…”
Section: Scheme 54 Preparation Of Fused Spirooxindoles 143mentioning
confidence: 99%
“…The reactivity of N-substituted pyridinium N-aminides through their interaction with a p-acid-activated alkyne also contrasts with the usual reactivity arising from their innate 1,3-C,N-dipolar character employed in av ariety of transformations. [42] Ar elated formal [3+ +2]-cycloaddition approachu sing acyl sulfonium ylides alongside alkynes under gold-catalysis was independently reported by the groups of Skrydstrup andM aulide. [43] Garzón and Davies established that the formal [3+ +2]-dipolar cycloaddition concept can be applied more widely to the formationo fo ther azoles.…”
Section: Aminides As Dipole Equivalentsmentioning
confidence: 99%
“…[3] In view of their importance, several synthetic methods have been developed. For example, indazolo[2,3-a]quinolines could be obtained through the aryne [3 + 2] dipolar cycloaddition reactions, [4] the PPh 3 -mediated reductive cyclization of 2-(o-nitrophenyl)quinolines, [5] and the Pd-catalyzed tandem cross-coupling of 2-(o-iodophenyl)-2H-indazole with organozinc reagents. [6] While the above methods are effective, they usually suffer from the use of complex starting materials, limited substrate scope or multistep operation.…”
Section: Introductionmentioning
confidence: 99%
“…J = 8 4. Hz, 1H);13 C NMR (CDCl 3 , 100 MHz) δ 13.8, 61.8, 117.1, 117.6, 117.9, 121.1, 121.7, 121.8, 123.3, 125.8, 126.3, 126.9, 128.0, 129.5, 129.8, 130.0, 131.2, 132.0, 133.3, 134.5, 149.6, 166.9.…”
mentioning
confidence: 99%